Identity negotiation in student cross cultural communication in Madura: A semio pragmatic approach in multiethnic social space - Suryandari, Nikmah; Rahmawati, Farida Nurul; Kurniasari, Netty Dyah; Poernamasari, Nadya; Rakhmawati, Yuliana (Universitas Bunda Mulia, 2025)
This study examines how the identities of students from various ethnicities in Indonesia are negotiated and demonstrated in the context of cross-cultural communication in the campus environment in Madura. In a social space dominated by strong Madurese cultural values—including religiosity, patriarchal social structures, and honorary symbolism—students from non-Madurese backgrounds such as Papua, Javanese, Batak, and Betawi face the need to adjust their expressions of identity to be socially accepted without losing their identity. This study uses a semiopragmatic approach that combines three levels in identity construction: prefiguration (cultural reference), configuration (situational adjustment), and figuration (actual performance in interaction). Data were collected through in-depth interviews and participatory observation of 15 students representing different ethnicities. The results showed that students used a variety of adaptive strategies, such as controlling communication styles, using cross-cultural symbols (e.g. Islamic greetings as social greetings), humor, and non-verbal contributions in academic forums. Each strategy reflects the dynamics of identity negotiation that are not only interpersonal but also symbolic and political. This research contributes to understanding how identity is not simply culturally inherited, but constructed situationally and pragmatically in the space of social interaction. These findings have important implications for the development of inclusive campus policies, the design of intercultural training programs, and the strengthening of intercultural dialogue spaces in multiethnic higher education environments